Impact of Iron Deficiency Anemia on Hemoglobin A1c Levels in Diabetic and Non-Diabetic Pregnant Women - Aysun Firat; Doruk Cevdi Katlan; Nebahat Uzunay (IMR Press, 2024)
Background: Gestational diabetes mellitus (GDM) is a well-known risk factor for pregnancy complications. While hemoglobin A1c (HbA1c) is widely used as a glycemic control indicator, it is known to exhibit falsely low or high levels during gestation. The purpose of the present study is to analyze the fluctuations in HbA1c levels throughout pregnancy in diabetic (DM) and non-DM women with or without iron deficiency anemia (A). Methods: Medical records of pregnant women who were followed up in our obstetrics clinic between 2018 and 2022 were reviewed. Demographics, gestational history, and biochemistry values including fasting glucose, HbA1c, erythrocyte and iron metabolism indexes were recorded. Statistical analysis was carried out by Mann-Whitney U and Bonferroni corrected one-way analysis of variance (ANOVA) tests. Results: 670 pregnant women (32 ± 14.2 years) were included with matched subgroups. In the non-DM and non-A group, HbA1c exhibited a significant decrease towards mid-pregnancy (5.29 vs. 5.08%, p < 0.01), followed by a steep increase towards the second half of pregnancy, reaching its initial value (5.08 vs. 5.27%, p < 0.01). In the non-DM and A pregnant women, HbA1c decreased from 5.25 to 5.19% (p > 0.05) in first half, followed by a significant increase to 5.37% (p < 0.05) in the second half of pregnancy when serum ferritin values dropped to 5.03 ± 3 µg/mL (p < 0.01). As for DM and non-A group, a biphasic change in HbA1c level was also recorded, however not significant (6.05 vs. 5.81%, p > 0.05). However, in the DM and A group, HbA1c levels were higher (7.09 vs. 6.01%, p < 0.01), along with iron deficiency indicated by ferritin levels (4.7 ± 2.2 µg/mL, p < 0.01). Conclusions: HbA1c exhibits biphasic changes throughout pregnancy, characterized by decreases towards mid-pregnancy and subsequentincreases in the third trimester. Therefore, questioning HbA1c levels is warranted, considering the changes in maternal physiology in early gestation and the increasing need for iron in later period. Furthermore, iron deficiency anaemia seems to have significant impact on the reliability of HbA1c in both the non-DM and DM pregnant women.